The Application of Fiduciary Guarantee in the Perspective of Islamic Law - Wieke Dewi Suryandari (Jurnal Daulat Hukum, 2021)
The development of economic activity in the world has an impact on the development of people's quality of life, thus increasing the need for funding to meet these needs. In addition, the majority of Indonesian people who are Muslim automatically bring Islamic law into their daily life in various fields, including in economic activities. Fiduciary guarantees are possible in a murabahah contract if the financing company acts as a seller (trader) who sells goods on credit to consumers, so not as a provider of funds that owes to consumers. Fund-raising activities to support business activities in the community are closely related to credit matters, the consequence is the need for a guarantee or known as fiduciary. Fiduciary guarantees are conventional products that are set to provide protection for creditors, especially if the debtor defaults. Fiduciary guarantees, which cannot be fully applied to all financial institution systems in Indonesia, need to be studied several times, especially in the view of the Islamic religion that uses the sharia financial system. The focus of the study that is used as the formulation of the problem is What is the current position of the application of fiduciary guarantees in Indonesia? and how to apply fiduciary guarantee according to the perspective of Islamic law?. The results of the study show that the practice of implementing fiduciary in Indonesia has a very important position and must be fulfilled by financing service providers. Meanwhile, according to the Islamic view, there is no fiduciary guarantee in the aspects of Islamic law but the matter of guarantees can be equated with rahn. Thus, in Islamic Financial Institutions guided by rahn as a guarantee system for lending and borrowing activities in accordance with Islamic law, this is based on the word of Allah QS. Al-Baqarah verse 283 and Act No. 21 of 2008 concerning Islamic Banking.